Youth trained in primary drug prevention on a peer level. (March 2016) - Knopf, Alison
Abstract : The largest annual meeting devoted to primary substance abuse prevention is held every year by Community Anti‐Drug Coalitions of America (CADCA). One of the most notable aspects of this meeting, which features an impressive array of researchers and providers, is the cadre of youth leaders. These adolescents, ages from about 13 to 17, descend upon National Harbor, Maryland, every February for the CADCA National Leadership Forum. Melanee Piskai, a trainer for CADCA's National Youth Leadership Initiative, talked to CABL about her work.